اول ${{A}^{2}}$ را پیدا میکنیم:
${{A}^{2}}=\left[ \begin{matrix}
1 & 1 \\
3 & 2 \\
\end{matrix} \right]\left[ \begin{matrix}
1 & 1 \\
3 & 2 \\
\end{matrix} \right]=\left[ \begin{matrix}
4 & 3 \\
9 & 7 \\
\end{matrix} \right]$
حالا ${{({{A}^{2}})}^{-1}}$ را مییابیم:
${{({{A}^{2}})}^{-1}}=\frac{1}{28-27}\left[ \begin{matrix}
7 & -3 \\
-9 & 4 \\
\end{matrix} \right]=\left[ \begin{matrix}
7 & -3 \\
-9 & 4 \\
\end{matrix} \right]$
حالا باید ماتریس ${{({{A}^{2}})}^{-1}}$ را به شکل $aA-bI$ در آوریم:
$\begin{align}
& \left[ \begin{matrix}
7 & -3 \\
-9 & 4 \\
\end{matrix} \right]=a\left[ \begin{matrix}
1 & 1 \\
3 & 2 \\
\end{matrix} \right]-b\left[ \begin{matrix}
1 & 0 \\
0 & 1 \\
\end{matrix} \right] \\
& \Rightarrow \left[ \begin{matrix}
7 & -3 \\
-9 & 4 \\
\end{matrix} \right]=\left[ \begin{matrix}
a-b & a \\
3a & 2a-b \\
\end{matrix} \right] \\
& \Rightarrow \left\{ \begin{matrix}
a=-3 \\
a-b=7\Rightarrow b=-10 \\
\end{matrix} \right. \\
\end{align}$
بنابراین:
$ab=(-3)(-10)=30$